From Blueprint to Balance Sheet: The Importance of Sustainability Reports in Engineering Projects and Their Impact on Financial Performance - A Systematic Review - Sari, Sendi Nopita; Prasetya, Luhur Adi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the impact and strategies of integrating sustainability reporting (SR) on the financial performance of engineering projects through a Systematic Literature Review (SLR) approach using the SPAR-4-SLR model. A total of 25 selected articles published between 2019 and 2025 were analyzed using thematic synthesis with the assistance of NVivo 12 software. The results of the analysis indicate that SR not only enhances transparency but also makes a positive contribution to return on investment (ROI), cost efficiency, and investor confidence. The most effective reporting strategies generally use the Global Reporting Initiative (GRI) and Environmental, Social, and Governance (ESG) frameworks, often combined with digital technologies such as artificial intelligence (AI) and blockchain. However, stakeholder engagement still receives insufficient attention, despite data indicating that active community participation can reduce project rejection risks by up to 35%. An evaluation of the quality of the reviewed articles indicates that most use robust methodologies and produce consistent findings. As such, SR plays a crucial role in strengthening the sustainability governance and financial performance of engineering projects. The research findings recommend integrating data-driven and participatory SR approaches as core pillars in socially and environmentally responsible project management practices.